Appraising the revamped performance management system in Indian IT multinational enterprises: The employees' perspective. Issue 5 (31st March 2021) - Tripathi, Ritu; Thite, Mohan; Varma, Arup; Mahapatra, Gopal
Abstract: In recent times, leading information technology (IT) multinational enterprises claim to have abandoned many traditional features of their performance management systems (PMSs), including the bell curve. However, there is no published empirical study on how employees are perceiving the change. Using an inductive approach and an employee‐centric theoretical lens, we investigated employees' ( n  = 426) perceptions and satisfaction levels with the revamped PMS in three Indian IT services and business solutions multinational enterprises. Employees perceived the present purposes of PMS marginally more favorably than those in the past; however, the gap between the present and future aspirational perceived purposes of PMS was significantly much higher. Satisfaction levels with different dimensions of PMS and alignment of PMS with other human resource functions and leader‐member exchange were only modest. Employees mentioned goal setting and continuous feedback as the most positive features of the current PMSs, and transparency, 360° feedback, and adherence to timelines—as improvement areas. The results are indicative of a positive, but the only modest trend in employee satisfaction and perceptions. We discuss the implications of the findings for the employee‐centric theory and practice of PMS in the IT industry.